Formulation and Evaluation of Oro-Dispersible Doxycycline Tablets - Dubey, Krishna Kumar; Agrawal, Dilip; Khinchi, Mahaveer Prasad; Soni, Shankar Lal; Singh, Surya Pratap (Asian Journal of Pharmaceutical Research and Development, 2015)
The aim for designing these dosage forms, convenient to be manufactured and administered, free of side effects, offering immediate release and enhanced bioavailability, so as to achieve better patient compliance. Though oral drug delivery systems, preferably, tablets are the most widely accepted dosage forms, for being compact, offering uniform dose and painless delivery. Oral drug delivery remains the most preferred route for administration of various therapeutic agents. Novel ODT technologies address many patient and pharmaceutical needs such as enhanced life cycle management to convenient dosing particularly for pediatric, geriatric and psychiatric patients who have difficulty in swallowing (Dysphagia) conventional tablet and capsules. Technologies used for manufacturing of ODTs are either conventional technologies or patented technologies.Orodispersible tablets (ODTs), also known as fastmelt, quick melts, fast disintegrating have theunique property of disintegrating in the mouth inseconds without chewing and the need of water.The present study demonstrated potentials forrapid absorption, improved bioavailability,effective therapy and patient compliance.